Protective effect of saikosaponin D against gestational diabetes mellitus via regulating TLR4/MyD88/NF-κB and MAPK signaling pathway - Lu-Lu Wang; Chong Yang; Ye-Qing Su; Fang Wang (Asian Pacific Journal of Tropical Biomedicine)
Objective: To examine the protective effect of saikosaponin D against streptozotocin (STZ)-induced gestational diabetes mellitus in female rats. Methods: Intraperitoneal administration of STZ (40 mg/kg) was used for the induction of diabetes in pregnant rats, and rats orally received sikosaponin D (10, 20, and 40 mg/kg). The body weight, placental weight, fetal weight, fetal index, and various biochemical parameters, including antioxidant, glucose level, cytokines, and apoptosis parameters, were estimated. The expression levels of various mRNAs were also analyzed. Results: Saikosaponin D increased body weight and fetal weight while decreasing placental weight and placental index. Saikosaponin D significantly altered various biochemical parameters such as fasting blood glucose, glycated hemoglobin (HbA1c), hemoglobin, hepatic glycogen, advanced glycation end products, lipid parameters (total cholesterol, triglyceride, low density lipoprotein, high density lipoprotein, very low density lipoprotein), antioxidant parameters (superoxide dismutase, glutathione, glutathione peroxidase, malonaldehyde, catalase), inflammatory cytokines (tumor necrosis factor-a, interleukin-6, interleukin-1β, interleukin-10), apoptosis parameters (Bcl-2, Bax, caspase-3), resistin, adiponectin, leptin, intercellular adhesion molecule 1, vascular cell adhesion molecule-1, and monocyte chemotactic protein-1. Furthermore, saikosaponin D modulated the mRNA expression of TLR4, MyD88, NF-κB, NLRP3, TNF-α, 1L-6, CRP, SIRT1, and MAPK. Conclusions: Saikosaponin D exhibits a protective effect against STZ-induced gestational diabetes mellitus in rats via regulation of TLR4/ MyD88/NF-κB and MAPK signaling pathways.